Perioperative immunonutrition in patients undergoing liver transplantation: A randomized double‐blind trial. Issue 2 (5th January 2015) - Plank, Lindsay D.; Mathur, Sachin; Gane, Edward J.; Peng, Sze‐Lin; Gillanders, Lyn K.; McIlroy, Kerry; Chavez, Carolina Paras; Calder, Philip C.; McCall, John L.
<x xml:space="preserve">Abstract</x> Preliminary work suggested that perioperative immunonutrition (IMN) enriched in n‐3 fatty acids, arginine, and nucleotides may improve preoperative nutritional status, enhance postoperative recovery, and reduce postoperative infectious complications in patients undergoing liver transplantation (LT). The current study examined these outcomes in a double‐blind, randomized, controlled trial. Patients wait‐listed for LT (n = 120) were randomized to either supplemental (0.6 L/d) oral IMN or an isocaloric control (CON). Enteral IMN or CON was resumed postoperatively and continued for at least 5 days. The change in total body protein (TBP) measured by neutron activation from study entry until immediately prior to LT was the primary endpoint and TBP measurements were repeated 10, 30, 90, 180, and 360 days after LT. Infectious complications were recorded for the first 30 postoperative days. Nineteen patients died or were delisted prior to LT. Fifty‐two IMN and 49 CON patients received supplemental nutrition for a median (range) 56 (0‐480) and 65 (0‐348) days, respectively. Preoperative changes in TBP were not significant (IMN: 0.06 ± 0.15 [SEM]; CON: 0.12 ± 0.10 kg). Compared to baseline, a 0.7 ± 0.2 kg loss of TBP was seen in both groups at 30 days after LT (P < 0.0001) and, at 360 days, TBP had not increased significantly (IMN: 0.08 ± 0.19 kg; CON: 0.26 ± 0.23 kg). Infectious complications occurred in 31 (60%) IMN and 28 (57%) CON patients (P = 0.84). The median (range) postoperative hospital stay was 10 (5‐105) days for IMN and 10 (6‐27) days for CON patients (P = 0.68). Conclusion: In patients undergoing LT, perioperative IMN did not provide significant benefits in terms of preoperative nutritional status or postoperative outcome. (Hepatology 2015;61:639‐647)